Comparative Analysis of Phonetic Games and Traditional Methods of Teaching Phonetics for the Development of Cognitive Activity in Elementary School Students - Dedakhanov, Abdumalik (Indonesian Journal Publisher, 2025)
This study aims to evaluate the effectiveness of phonetic games compared to traditional methods of teaching phonetics in elementary school students, with a focus on enhancing cognitive activity. The research was conducted with 960 fifth-grade students from Andijan, Fergana, and Namangan regions of Uzbekistan. Students were divided into experimental and control groups. Data were collected using standardized tests, classroom observations, teacher interviews, and student surveys. The results demonstrate that students in the experimental group, who learned phonetics through phonetic games, achieved significantly higher improvements in their knowledge, motivation, and interest compared to the control group, which continued with traditional teaching methods. On average, the experimental group’s test scores increased from 40 to 65, while the control group only improved from 43 to 50. Moreover, 85% of the experimental group reported higher engagement and confidence in learning. The study concludes that phonetic games not only improve academic performance but also enhance students’ motivation, confidence, and classroom behavior. They create an interactive and enjoyable learning environment that reduces stress and fosters deeper understanding. The findings suggest that phonetic games should be more widely integrated into elementary school curricula to improve the effectiveness of phonetics instruction.